Plant community responses to integrating livestock into a reduced‐till organic cropping system. Issue 3 (8th March 2021) - Larson, Christian D.; Menalled, Fabian D.; Lehnhoff, Erik A.; Seipel, Tim
Abstract: The problems with herbicide‐ and tillage‐based weed management in agriculture are well documented and have precipitated research into finding alternatives. Integrating livestock grazing into organic agroecosystems has benefits and is a viable method for terminating cover crops, yet its impacts on weed communities are largely unknown. This lack of knowledge is particularly true in semi‐arid environments, including the Northern Great Plains, where we conducted our research. We compared weed community responses (biomass, species richness, Simpson's diversity, composition) of a sheep‐grazed organic cropping system with those of two contrasting cropping systems (high input conventional no‐till, tilled organic) across a five‐year crop rotation (safflower, sweet clover, winter wheat, lentils, winter wheat). We found that the conventional no‐till and tilled organic systems suppressed weed biomass and reduced species richness and diversity, while the grazed organic resulted in higher weed biomass, species richness, and diversity. During the first two years of the study, the composition of the two organic communities were distinct from the conventional no‐till communities but were indistinguishable from one another. Over the final three years of the study, grazed organic communities were tightly grouped and became distinct from both the tilled and conventional communities. We found that weed biomass and diversity were highest in the sweet clover and lowest in the winter wheat. The spring annual crops, safflower and lentil, demonstrated similar weed biomass, species richness, and composition. Our findings indicate that integrating livestock into cropping systems alters plant communities and increases the agroecosystem plant biodiversity of semi‐arid organic farming and that specific crops interact with cropping systems to alter agroecosystem plant communities. However, the increase in weed biomass associated with our grazing treatment makes this approach impractical as the sole weed management strategy and necessitates that integrating livestock into semi‐arid organic cropping systems must be part of a larger integrated weed management program.